Analisis Kepuasan Orang Tua terhadap Kualitas Pelayanan SD Birrul Walidain Muhammadiyah Sragen - Tutik Ernawati; Ari Qudriyati; Harun Joko Prayitno; Dhany Efita Sari (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
The quality of educational services in elementary schools is an important factor in building trust and satisfaction among parents as the primary stakeholders. The increasing expectations of parents toward educational services, which focus not only on academic outcomes but also on the quality of the learning process, encourage schools to evaluate the level of parental satisfaction. This study aims to analyze the level of parents’ satisfaction with the quality of services at SD Birrul Walidain Muhammadiyah Sragen and to identify service aspects that need improvement. The study employed a descriptive quantitative approach with a survey design. The respondents consisted of 98 parents of first-grade students, and data were collected through a Google Form–based questionnaire. Data analysis was conducted using descriptive statistical techniques (percentages and means) as well as Importance Performance Analysis (IPA) to measure the gap between service expectations and performance. The results showed that the overall level of parents’ satisfaction was categorized as good, with indicator conformity levels above 85%. The main strengths were found in teachers’ attention and the provision of learning motivation. However, several aspects still need improvement, particularly in teaching methods, assignment distribution, and opportunities for students to ask questions in class. These findings emphasize the importance of improving learning quality as a key factor in increasing parents’ satisfaction. Nevertheless, the results of this study are limited to first-grade respondents and therefore cannot yet be generalized to all grade levels.